Collateral and capital structure - Rampini, Adriano A.; Viswanathan, S. (Journal of Financial Economics, 2013)
We develop a dynamic model of investment, capital structure, leasing, and risk management based on firms' need to collateralize promises to pay with tangible assets. Both financing and risk management involve promises to pay subject to collateral constraints. Leasing is strongly collateralized costly financing and permits greater leverage. More constrained firms hedge less and lease more, both cross-sectionally and dynamically. Mature firms suffering adverse cash flow shocks may cut risk management and sell and lease back assets. Persistence of productivity reduces the benefits to hedging low cash flows and can lead firms not to hedge at all.